Integrin subtypes and nanoscale ligand presentation influence drug sensitivity in cancer cells - Young, Jennifer; Hua, Ximeng; Somsel, Heidi; Reichart, Florian; Kessler, Horst; Spatz, Joachim P. (Nano letters, 2020)
Cancer cell-matrix interactions have been shown to enhance cancer cell survival via the activation of pro-survival signaling pathways. These pathways are initiated at the site of interaction, i.e., integrins, and thus, their inhibition has been the target of therapeutic strategies. Individual roles for fibronectin-binding integrin subtypes αvβ3 and α5β1 have been shown for various cellular processes; however, a systematic comparison of their function in adhesion-dependent chemoresistance is lacking. Here, we utilize integrin subtype-specific peptidomimetics for αvβ3 and α5β1, both as blocking agents on fibronectin-coated surfaces and as surface-immobilized adhesion sites, in order to parse out their role in breast cancer cell survival. Block copolymer micelle nanolithography is utilized to immobilize peptidomimetics onto highly ordered gold nanoparticle arrays with biologically relevant interparticle spacings (35, 50, or 70 nm), thereby providing a platform for ascertaining the dependence of ligand spacing in chemoprotection. We show that several cellular properties—morphology, focal adhesion formation, and migration—are intricately linked to both the integrin subtype and their nanospacing. Importantly, we show that chemotherapeutic drug sensitivity is highly dependent on both parameters, with smaller ligand spacing generally hindering survival. Furthermore, we identify ligand type-specific patterns of drug sensitivity, with enhanced chemosurvival when cells engage αvβ3 vs α5β1 on fibronectin; however, this is heavily reliant on nanoscale spacing, as the opposite is observed when ligands are spaced at 70 nm. These data imply that even nanoscale alterations in extracellular matrix properties have profound effects on cancer cell survival and can thus inform future therapies and drug testing platforms.
Gesehen am 23.04.2020